Prospective study of the Transurethral Suprapubic endo-Cystostomy (T-SPEC(®)): an ‘inside-out’ approach to suprapubic catheter insertion - Flynn, Brian J. (Int Urol Nephrol, 2014)
OBJECTIVES: To prospectively evaluate the new medical device Transurethral Suprapubic endo-Cystostomy (T-SPeC(®)), used for suprapubic catheter (SPC) placement via the transurethral (inside-to-out) approach, and examine the 30-day outcomes in the first US series. METHODS: IRB approval was obtained for this prospective study. We evaluated the first 114 consecutive cases of SPC placement using the T-SPeC(®) device by a single surgeon at in a 20-month period. We excluded patients who underwent alternative approaches to suprapubic catheter placement including open abdominal approach (12) and percutaneous approach (5). Preoperative patient demographics, operative detail, success rate and 30-day complication rate were recorded. RESULTS: We successfully placed an 18 Fr suprapubic catheter using the T-SPeC(®) device in 98.2 % of patients. During the procedure, the capture housing was missed twice. The mean patient age was 56.6, BMI 29.4 kg/m(2), skin to bladder distance 6.7 cm and operative time 3.6 min. There were 12 postoperative complications within 30 days of the procedure including urinary tract infections (6), SPC exit site infection (2), SPC blockage (2) and catheter expulsion (2). There were no Clavien–Dindo grade III–IV complications such as re-operation, small bowel injury, hemorrhage or death. CONCLUSION: The T-SPeC(®) device is a novel, simple, accurate and minimally invasive device for SPC insertion from an inside-to-out approach. Our prospective study demonstrates that the T-SPeC(®) device can be placed safely and efficiently in a variety of patients with a need for urinary drainage.